Stay alive - Bell, William Brent; Matthew, Bell (Hollywood Pictures Home Entertainment Distributed by Buena Vista Home Entertainment ; distributed in the Philippines by MagnaVision, 2006)
After their friend is brutally murdered, a group of friends find themselves in possession of a video-game called "Stay Alive." The game is based on a blood-curdling true story of a 17th century noblewoman who was known as the Blood Countess. Knowing that they should not play with the game, the friends play anyway and realize that once they die in the game, they die for real. As their numbers begin dropping and as they begin dying in the ways they died in the game, the remaining friends realize they must defeat the Blood Countess or accept their deadly fates.